The Prehispanic Ethnobotany of Paquimé and its neighbors - book review - Kappuw, Fridholin Yacob (Ethnobotany Research and Applications, 2025)
The Prehispanic Ethnobotany of Paquimé and Its Neighbors, authored by Paul E. Minnis and Michael E. Whalen. The University of Arizona Press, 2020, pp 177, $67.00 (Hardcover), $63.65 (eBook), ISBN 9780816540792 (Hardcover), ISBN 0816540799 (eBook). The Prehispanic Ethnobotany of Paquimé and Its Neighbors, authored by Paul E. Minnis and Michael E. Whalen, offers a comprehensive exploration of the relationships between ancient human communities and their botanical environments in northwestern Chihuahua, Mexico. Covering the period approximately AD 1200 - 1450, known as the Medio period, this book emphasizes economic, ecological, and cultural dimensions of plant use by prehistoric societies in the region. In revisiting the findings of the Joint Casas Grandes Expedition (JCGE), the authors critique the prevailing narrative that positions Paquimé primarily as a cultural conduit between Mesoamerica and the U.S. Southwest. Instead, they propose a more localized and ecological perspective, arguing that the exceptional agricultural productivity of the Río Casas Grandes valley enabled the development of food surpluses, which in turn supported complex sociopolitical structures such as communal feasting. Structured across five chapters, the authors begin by placing Paquimé within a broader environmental and archaeological framework, clearly detailing the area's diverse ecosystems - from mountain forests to arid desert grasslands - and climatic variability.